1982
DOI: 10.1111/j.2044-8295.1982.tb01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Social factors in conservation

Abstract: This study is a partial replication, with variations, of the experiments of McGarrigle & Donaldson (1975) and Light et al. (1979). Sixty-four 5-year-old children were tested on traditional Piagetian tests of conservation of number under a standard control condition, and one of two experimental conditions: one (M) in which the task materials were apparently accidentally transformed by a mischievous monkey manipulated by a second experimenter, and another ( I ) in which the transformation was made to appear ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
(9 reference statements)
0
9
0
1
Order By: Relevance
“…Research has shown that conservation questions can be problematic for young children and that when the question is altered these children perform better (Hargreaves et al, 1982). That is, framing the conservation question as an appearance-reality question facilitates children's understanding of what is actually being asked of them (e.g., "Are they really different or is there still the same amount?"…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that conservation questions can be problematic for young children and that when the question is altered these children perform better (Hargreaves et al, 1982). That is, framing the conservation question as an appearance-reality question facilitates children's understanding of what is actually being asked of them (e.g., "Are they really different or is there still the same amount?"…”
Section: Discussionmentioning
confidence: 99%
“…The ecological validity of standard conservation tasks has been identified as a factor in young children's poor performance (Donaldson, 1978;Gelman, 1978), and linguistic difficulties are said to contribute to the failure of children younger than 7 years (Hargreaves, Molloy & Pratt, 1982;Rose & Blank, 1974). The ecological validity of standard conservation tasks has been identified as a factor in young children's poor performance (Donaldson, 1978;Gelman, 1978), and linguistic difficulties are said to contribute to the failure of children younger than 7 years (Hargreaves, Molloy & Pratt, 1982;Rose & Blank, 1974).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports have stated that acquisition can begin sooner (between 4-and 6-year-olds) if task methods are properly designed or training is conducted (Seigler, 2016;Gelman, 1969;McGarrigle & Donaldson, 1974;Light, Buckingham, & Robbins, 1979;Hargreaves, Molloy, & Pratt, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many studies concerning pragmatics relate to this point (Goswami, 1998;Donaldson, 1978;Rose & Blank, 1974;Siegal, 1991;McGarrigle & Donaldson, 1974;Dehaene, 1997). Furthermore, some reports have stated that acquisition can happen sooner, at between 4 and 6 years, if task methods are properly designed or practiced (Siegler, 2016;Gelman, 1969;McGarrigle & Donaldson, 1974;Light, Buckingham, & Robbins, 1979;Hargreaves, Molloy, & Pratt, 1982). However, designing tasks often changes questions' contexts, and some researchers have held that such changed questions do not actually examine Piaget's conservation concept (Miller, 1982;Nakagaki, 1990;Goswami, 1998).…”
Section: Introductionmentioning
confidence: 99%